Social transformation, collective health and community-based arts: 'Buen Vivir' and Ecuador's social circus programme. Issue 6 (3rd July 2019) - Spiegel, J. B.; Ortiz Choukroun, B.; Campaña, A.; Boydell, K. M.; Breilh, J.; Yassi, A.
ABSTRACT: Worldwide, interest is increasing in community-based arts to promote social transformation. This study analyzes one such case. Ecuador's government, elected in 2006 after decades of neoliberalism, introduced Buen Vivir ('good living' derived from the Kichwan sumak kawsay ), to guide development. Plans included launching a countrywide programme using circus arts as a sociocultural intervention for street-involved youth and other marginalised groups. To examine the complex ways by which such interventions intercede in 'ways of being' at the individual and collective level, we integrated qualitative and quantitative methods to document relationships between programme policies over a 5-year period and transformations in personal growth, social inclusion, social engagement and health-related lifestyles of social circus participants. We also conducted comparisons across programmes and with youth in other community arts. While programmes emphasising social, collective and inclusive pedagogy generated significantly better wellbeing outcomes, economic pressures led to prioritising productive skill-building and performing. Critiques of the government's operationalisation of Buen Vivir, including its ambitious technical goals and pragmatic economic compromising, were mirrored in social circus programmes. However, the programme seeded a grassroots social circus movement. Our study suggests that creative programmes introduced to promote social transformation can indeed contribute significantly to nurturing a culture of collective wellbeing.